African Primary Care Research: Qualitative data analysis and writing results - Langalibalele H. Mabuza; Indiran Govender; Gboyega A. Ogunbanjo; Bob Mash (AOSIS, 2014)
This article is part of a series on African primary care research and gives practical guidance on qualitative data analysis and the presentation of qualitative findings. After an overview of qualitative methods and analytical approaches, the article focuses particularly on content analysis, using the framework method as an example. The steps of familiarisation, creating a thematic index, indexing, charting, interpretation and confirmation are described. Key concepts with regard to establishing the quality and trustworthiness of data analysis are described. Finally, an approach to the presentation of qualitative findings is given.